Study of the ψ2(3823) and χc1(3872) states in B+ → (J/ψπ+π-) K+ decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; Dziewiecki, Michal; Frau, Giulia; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2020)
The decays B+ → J/ψπ+π−K+ are studied using a data set corresponding to an integrated luminosity of 9 fb−1 collected with the LHCb detector in proton-proton collisions between 2011 and 2018. Precise measurements of the ratios of branching fractions with the intermediate ψ2(3823), χc1(3872) and ψ(2S) states are reported.
Im Titel sind "2" und "c1" tiefgestellt, die "+" und "-" hochgestellt
LHCb Collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, S. Braun, M. Dziewiecki, G. Frau, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, J. Hu, M. Kecke, R. Kopecna, B. Leverington, P. Li, H. Malygina, J. Marks, S. Neubert, A. Piucci, N. Skidmore, S. Stemmle, D.J. Unverzagt, U. Uwer, L. Witola, A. Zhelezov [und 937 weitere]
Gesehen am 05.11.2020